Electronic warfare target location methods - Poisel, Richard (Artech House, 2012)
Describing the mathematical development underlying current and classical methods of geolocating electronic systems that are emitting, this newly revised and greatly expanded edition of a classic Artech House book offers practical guidance in electronic warfare target location. The Second Edition features a wealth of additional material including new chapters on time delay estimation, direction finding techniques, and the MUSIC algorithm. This practical resource provides you with critical design information on geolocation algorithms, and establishes the fundamentals of existing algorithms as a launch point for further algorithm development